Fifty Key Figures in ManagementFifty Key Figures in Management, by Witzel Morgen. London: Routledge, 2003. - Duncan, W. Jack (Academy of Management Review, 2004)
A review is presented of the book ?Fifty Key Figures in Management,? by Morgen Witzel.